The role of twinning and stacking fault-induced plasticity on the mechanical properties of aluminum-lithium-graphene nanocomposites - Sara I. Ahmad; Atef Zekri; Khaled M. Youssef (Nanocomposites, 2024)
In this study, the synthesis-structure-property relationship of graphene-reinforced Al matrix nanocomposites was investigated. The Al-Li-GNPs nanocomposite was synthesized to attain both high strength and good ductility. The incorporation of GNPs as a reinforcement in the Al-based matrix provided a nanocomposite structure for an integrated strengthening effect. To promote plasticity and maintain good ductility, the nanocrystalline Al matrix was alloyed with Li to reduce its stacking fault energy and promote additional deformation mechanisms. The compressive yield strength (CYS) increased from 88 MPa for the starting Al to 403 MPa for the Al-Li-GNPs nanocomposites with 1.0 wt% GNPs. Fracture analysis indicated that the synthesized nanocomposite exhibited a ductile nature and significant plastic deformation. Based on microscopic analysis, the enhanced strength of the Al-Li-GNPs nanocomposite was attributed to grain refinement, load transfer, and strain hardening. The good ductility, on the other hand, was attributed to dislocation slipping, the formation of stacking faults, and twinning.